Agama di Ruang Publik: Kajian Kritis terhadap Pemikiran Furshet, Casanova, dan Sherkat - Hanifa Maulidia (Sociology Department Of Syiah Kuala University, 2018)
AbstractReligion has always been an interesting talk of sociologists, both in public and private spaces. This paper discusses the study of religion in the public space are written by Furshet, et al., Casanova, and Sherkat. First, Furseth et al. which explains religion in the five forms of discussion, namely the legal religion in a country, civil religion, religious nationalism, public religion and religious legitimacy, and political power that all take place in the political arena. Secondly, Casanova invites us to be more critical and able to distinguish three meanings of secularization with different connotations, namely secularization as a process of declining beliefs and religious practices in modern society, secularization as a form of privatization of religion, and secularisation as a distinction between the secular space of the state, and knowledge. Third, Sherkat describes religious socialization as an interactive process in which social agents can influence an individual's religious beliefs and religious understanding. These three writings look at religion in the public sphere from a different point of view, which makes us more critical in seeing and understanding a religion.Keywords: Religion, Secular, Public SpaceAbstrakAgama selalu menjadi pembicaraan menarik para sosiolog, baik di ruang publik maupun privat. Tulisan ini membahas tentang kajian agama di ruang publik yang dikemukakan oleh Furshet, dkk., Casanova, dan Sherkat. Pertama, Furseth dkk. yang menjelaskan agama dalam lima bentuk bahasan, yaitu agama legal dalam sebuah negara, civil religion, religious nationalism, agama publik dan legitimasi agama, dan political power yang semuanya berlangsung dalam arena politik. Kedua, Casanova yang mengajak kita untuk lebih kritis dan mampu membedakan tiga makna sekulerisasi dengan konotasi yang berbeda, yaitu sekulerisasi sebagai proses kemunduran keyakinan dan praktek agama dalam masyarakat modern, sekulerisasi sebagai bentuk privatisasi agama, dan sekulerisasi sebagai pembedaan antara ruang sekuler yaitu negara, ekonomi, dan pengetahuan. Ketiga, Sherkat menjelaskan tentang sosialisasi agama yaitu proses interaktif di mana para agen sosial dapat mempengaruhi keyakinan beragama seorang individu dan pemahaman agamanya. Ketiga tulisan tersebut melihat agama di ruang publik dari sudut pandang yang berbeda, yang membuat kita lebih kritis dalam melihat dan memandang sebuah agama.Kata Kunci: Agama, Sekuler, Ruang Publik